Marinesque (Loupian, Hérault) : un relais routier sur la voie Domitienne - Iouri Bermond; Michel Christol; Michel Feugère; Christophe Pellecuer; Corinne Sanchez (Gallia)
Excavations conducted since 2004 alongside the Marinesque, a small intermittent river, have uncovered a long stretch of the Via Domitia as well as a small bridge-like structure. Buildings uncovered on both banks of the river were part of a complex in operation in the 1st century BC. They were most likely relay stations given their proximity to the road and the existence of certain facilities such as cooking areas. This hypothesis is confirmed by the specific configuration of objects found, with a significant quantity of tableware (especially drinking vessels), and greater quantities of non-Mediterranean Gallic coinage than found in most regional sites. The construction of the site, in the second quarter of the 1st century BC, could be considered a local initiative on the outskirts of lands that had been cultivated since the Iron Age in order to take advantage of its proximity to a public road. The repeated flooding of the river and the development of new forms of land ownership – legal evidence of which was discovered in the form of a boundary marker – most likely led to the site being abandoned at the beginning of the Early Empire.